التمويل الإسلامي للمشروعات متناهية الصغر والصغيرة وتأثيراته للحد من مشكلة البطالة كمدخل للتنمية الاقتصادية - بالرمان، نوري محمد رمضان; لوبيس، أسموليادي; ابن مهاد، ريزال بن موازير (جامعة المدينة العالمية, 2023)
تهدف هذه الدراسة إلى التعريف بأهم صيغ التمويل الإسلامية وبيان خصائصها ومزاياها في تمويل المشروعات المتناهية الصغر والصغيرة كحل لأهم المشاكل والمعوقات التي تواجه نجاحها باعتبارها من أهم دعائم ومحركات النهضة الاقتصادية، وناقشت مفهوم هذه المشروعات وبيان أهميتها في التنمية الاقتصادية، من خلال مساهمتها في زيادة الدخل والقيمة المضافة للناتج القومي المحلي، وفي الحد من مشكلة البطالة التي تعيق التنمية، وعلاج آثارها السلبية على كيان الدولة من الناحية الاقتصادية والاجتماعية واستقرارها السياسي والأمني، وذلك بتوفيرها فرص التوظيف للعاطلين عن العمل، وذكر تجارب بعض الدول المختلفة في هذا المجال، وتطرقت لتوصيف عام للتنمية الاقتصادية. سلكت الدراسة المنهج الوصفي لتغطية محاورها المختلفة. وتوصلت إلى مجموعة من النتائج أهمها أن التمويل الإسلامي متنوع في أشكاله؛ مما يجعله قادرا على تمويل مختلف قطاعات الأنشطة الاقتصادية وخصوصا المشروعات المتناهية الصغر والصغيرة، تتميز المشروعات المتناهية في الصغر والصغيرة بمجموعة من الخصائص تجعلها تساهم بشكل كبير في الحد من مشكلة البطالة كمدخل للتنمية الاقتصادية. أوصت الدراسة بضرورة تشجيع إقامة المشروعات المتناهية الصغر والصغيرة بهـدف امتصاص البطالة، وإنشاء هيئة حكومية لرعايتها، ووضع الخطط والسياسات والاستراتيجيات والبرامج التدريبية لها، ومنحها الإعفاءات من الضرائب والرسوم الجمركية وتعزيز قدرتها التنافسية. This study introduced the importance of the Islamic financing formula and explained its characteristics and advantages in financing micro and small community projects and establishing and developing new ones to provide solutions to the challenging aspects of the Islamic financing system as a pillar and driver of the economic revival. The study discussed the concept of Islamic Financing projects and their essential role in economic development through their contribution to increasing financial income and adding value to local and national products. To reduce the problem of unemployment hindering the growth of a community and its adverse effects on the state entity in terms of economic, social, political and security stability by providing employment opportunities for the unemployed. The study also narrated the experiences of some countries that have implemented the Islamic financing system and how they have dealt with the economic development challenges. The study has implemented a descriptive approach. A set of findings were reached at the end of the study, among which is that Islamic finance has a diverse nature. It makes it able to finance various sectors of economic activities, especially micro and small projects, which are characterized by a set of characteristics, among which is to reduce the problem of unemployment as an entry point for economic development. The study also provides a set of recommendations, among which is to encourage the establishment of micro and small projects to solve the unemployment challenges, to establish a government agency in charge of the program, and also to develop plans, policies, strategies, and training programs for the success of the Islamic Finance system. Lastly, to grant them additional benefits and exemptions from taxes, customs duties, and other fees to motivate them and enhance their competitiveness.
Keywords: تمويل المشروعات -- المشروعات الصغيرة -- ظاهرة البطالة -- الصيرفة الإسلامية